Perspective of 3D culture in medicine: transforming disease research and therapeutic applications - Park, Chan Hum; Park, Jung Ho; Suh, Yong Joon (Frontiers in Bioengineering and Biotechnology, 2024)
3D cell culture is gaining momentum in medicine due to its ability to mimic real tissues (in vivo) and provide more accurate biological data compared to traditional methods. This review explores the current state of 3D cell culture in medicine and discusses future directions, including the need for standardization and simpler protocols to facilitate wider use in research.Purpose3D cell culture develops life sciences by mimicking the natural cellular environment. Cells in 3D cultures grow in three dimensions and interact with a matrix, fostering realistic cell behavior and interactions. This enhanced model offers significant advantages for diverse research areas.MethodsBy mimicking the cellular organization and functionalities found in human tissues, 3D cultures provide superior platforms for studying complex diseases like cancer and neurodegenerative disorders. This enables researchers to gain deeper insights into disease progression and identify promising therapeutic targets with greater accuracy. 3D cultures also play a crucial role in drug discovery by allowing researchers to effectively assess potential drugs’ safety and efficacy.Results3D cell culture’s impact goes beyond disease research. It holds promise for tissue engineering. By replicating the natural tissue environment and providing a scaffold for cell growth, 3D cultures pave the way for regenerating damaged tissues, offering hope for treating burns, organ failure, and musculoskeletal injuries. Additionally, 3D cultures contribute to personalized medicine. Researchers can use patient-derived cells to create personalized disease models and identify the most effective treatment for each individual.ConclusionWith ongoing advancements in cell imaging techniques, the development of novel biocompatible scaffolds and bioreactor systems, and a deeper understanding of cellular behavior within 3D environments, 3D cell culture technology stands poised to revolutionize various aspects of healthcare and scientific discovery.